Information Potential of Changses on Agroclimate Zonation in Palu Valley Central Sulawesi - Alfiandy, Solih; Hadid, Abdul; Syakur, Abdul (Universitas Tadulako, 2021)
The information of agroclimate zonation according by Oldeman and Schmidt – Ferguson, and the potential of changes has never been done before. So, the purpose of this study is to determine the potential of agroclimate zonation changes according by Oldeman and Schmidt – Ferguson in the Palu Valley Central Sulawesi. The method used in this study is by counting the number of wet and dry months based on observation and prediction data results using ANN. The results of zonation according by Oldeman and Schmidt – Ferguson show that 2 points have the potential to changes and 2 points are fixed. The zonation by Oldeman at the Stageof Palu which was originally type E5 changes to E2 and Tawaili from E5 changes to E3, then based on Schmidt – Ferguson at Stageof Palu which was originally type F changes to E and Tawaili from F changes to D. This research found that the potential for agroclimate zonation of changes according to Oldeman and Schmidt Ferguson in the upcoming period has the potential will changes towards wetness due to the increasing number of humid and wet months, and the decreasing number of dry months.